Bacterial Communities in Tissues and Surficial Mucus of the Cold-Water Coral Paragorgia arborea - Weiler, Bradley A.; Verhoeven, Joost T. P.; Dufour, Suzanne C. (Frontiers in Marine Science, 2018)
Coral bacterial associates can play important functional roles for the holobiont, such as nitrogen cycling, nutrient processing, and supporting immunity. While bacteria found within the microbiome of corals may benefit the host, they can also be linked to pathogenesis. In the deep-sea, cold-water corals, like their warm shallow-water counterparts, host bacterial communities, but have received little attention due to logistical constraints in sampling. In particular, bacteria associated with surficial mucus of cold-water corals have not yet been investigated. Here, tissue and mucus samples of Paragorgia arborea were collected from three submarine canyons along the continental slope of the Gulf of Maine. Bacterial DNA was extracted from tissue and mucus samples and sequencing of the V6-V8 hypervariable region of the 16S rRNA gene was performed using Illumina MiSeq. The bacterial communities associated with P. arborea compartments (tissue and mucus) and sampling locations (canyon) differed significantly in composition. Proteobacteria, Tenericutes, and Spirochaetes were the dominant phyla across the majority of coral tissue samples, with Gammaproteobacteria and Alphaproteobacteria identified as the largest Proteobacteria contributors across all samples. OTUs belonging to the taxa Spirochaeta, Mycoplasma, Flavobacteriaceae, Terasakiellaceae, Campylobacterales and Rickettsiales were identified as biomarkers (bacterial taxa significantly more abundant in a specific coral microhabitat) of P. arborea tissues, while Paracoccus was a biomarker of P. arborea mucus. Many of the recovered biomarker taxa may be involved in nitrogen cycling. Representatives from several bacterial families (Vibrionaceae, Campylobacteraceae, Rhodobacteraceae, Flavobacteraceae, and Burkholderiaceae) previously reported in diseased scleractinians, were present in P. arborea as rare bacterial taxa. Characterizing the bacterial associates present in visibly healthy coral colonies provides a benchmark of dominant and rare bacterial groups present in the cold-water coral holobiont. This is the first characterization of bacterial groups associated with P. arborea, examining both tissue- and mucus-specific communities.